PHAEODACTYLUM TRICORNUTUM MICROALGAE GROWTH RATE IN HETEROTROPHIC AND MIXOTROPHIC CONDITIONS - Morais, K. C. C.; Ribeiro, R. L. L.; Santos, K. R.; Taher, D. M.; Mariano, A. B.; Vargas, J. V. C. (Revista de Engenharia Térmica, 2009)
The Brazilian National Program for Biofuel Production has been encouraging diversification of feedstock for biofuel production. One of the most promising alternatives is the use of microalgae biomass for biofuel production. The cultivation of microalgae is conducted in aquatic systems, therefore microalgae oil production does not compete with agricultural land. Microalgae have greater photosynthetic efficiency than higher plants and are efficient fixing CO2. The challenge is to reduce production costs, which can be minimized by increasing productivity and oil biomass. Aiming to increase the production of microalgae biomass, mixotrophic cultivation, with the addition of glycerol has been shown to be very promising. During the production of biodiesel from microalgae there is availability of glycerol as a side product of the transesterification reaction, which could be used as organic carbon source for microalgae mixotrophic growth, resulting in increased biomass productivity. In this paper, to study the effect of glycerol in experimental conditions, the batch culture of the diatom Phaeodactylum tricornutum was performed in a 2-liter flask in a temperature and light intensity controlled room. During 16 days of cultivation, the number of cells per ml was counted periodically in a Neubauer chamber. The calculation of dry biomass in the control experiment (without glycerol) was performed every two days by vacuum filtration. In the dry biomass mixotrophic experiment with glycerol concentration of 1.5 M, the number of cells was assessed similarly in the 10th and 14th days of cultivation. Through a volume element methodology, a mathematical model was written to calculate the microalgae growth rate. Was used an equation that describes the influence of irradiation and concentration of nutrients in the growth of microalgae. A simulation time of 16 days was used in the computations, with initial concentration of 0.1 g l-1. In order to compare simulation data with experimental data, we calculated the dry weight in 8 points in the course of sixteen days. In this way, it was possible to assess graphically biomass concentration versus time through the experiments and by numerical simulation. It was identified that the simulation results were consistent with the experiments and that the addition of glycerol greatly influenced the growth of microalgae. In the present analysis, the glycerol added increased 30% in biomass.